The Southeastern Librarian, Vol.48, No.2, Summer 1999 - Sears, Debra (The Southeastern Library Association, 1999)
The Southeastern Librarian, Vol.48, No.02, 1999. Periodical.
1 electronic record. 56 pages. Scanned from original document. Contents Include: President's Message- 13, From the Editor- 14, Margaret Pugh- The Virtual Southeast- 15, Calendar- 17, Karen Reichardt and Betsey Carter- Teaching the Teachers: The Library's Role In Using the Internet Effectively- 19, Mary Edna Anders- The Southeastern Library Association, 1920-1950- 23, Philip Jones- "The Poor, Sick, Ugly, Raving Lunatic": Early Response to Flannery O'Connor's Wise Blood- 57, Gail Kwak- Everything I Need to Know I Learned from the Census: My Life as a Government Documents Librarian- 64, Web site and Listserv Information- 56, Guidelines for Submissions to the Southeastern Librarian- 66
Keywords: Periodicals | Southeastern Library Association